1989
DOI: 10.1111/j.1471-4159.1989.tb08542.x
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Astrocytes and Neurons Synthesize and Secrete Carboxypeptidase E, a Neuropeptide‐Processing Enzyme

Abstract: Carboxypeptidase E (EC 3.4.17.10) is a carboxypeptidase B-like enzyme associated with the biosynthesis of many peptide hormones and neurotransmitters. Media collected from cultured astrocytes contain a carboxypeptidase E-like activity. Cultured astrocytes secrete approximately 73% of their cellular level of carboxypeptidase E per hour, and secretion is not substantially influenced by 35 mM KCl. In contrast, neurons secrete only 29% of their cellular carboxypeptidase E per hour, but secretion increases to 86% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 25 publications
4
23
0
Order By: Relevance
“…These results suggest that CPE mRNA localization in the central nervous system corresponds to the distribution of neurotransmitter-synthesis neurons, further indicating the role of CPE in neuropeptide processing (58). In addition, CPE mRNA is localized in reactive glia as well, which is consistent with a study showing that cultured astrocytes are able to synthesize and secrete CPE (60). Since cultured astrocytes can express a number of neuropeptides, such as proenkephlin (60), somatostatin (61) and angiotensinogen (62), this result suggests that CPE may process neuropeptides in glia.…”
Section: Propertiessupporting
confidence: 90%
See 1 more Smart Citation
“…These results suggest that CPE mRNA localization in the central nervous system corresponds to the distribution of neurotransmitter-synthesis neurons, further indicating the role of CPE in neuropeptide processing (58). In addition, CPE mRNA is localized in reactive glia as well, which is consistent with a study showing that cultured astrocytes are able to synthesize and secrete CPE (60). Since cultured astrocytes can express a number of neuropeptides, such as proenkephlin (60), somatostatin (61) and angiotensinogen (62), this result suggests that CPE may process neuropeptides in glia.…”
Section: Propertiessupporting
confidence: 90%
“…In addition, CPE mRNA is localized in reactive glia as well, which is consistent with a study showing that cultured astrocytes are able to synthesize and secrete CPE (60). Since cultured astrocytes can express a number of neuropeptides, such as proenkephlin (60), somatostatin (61) and angiotensinogen (62), this result suggests that CPE may process neuropeptides in glia. However, high level of CPE mRNA is also shown in some neurons not presently known to express specific neuropeptides (59), implying that in these cells CPE may have functions other than peptide processing, such as transporting neurotransmitter vesicles, or there may be undiscovered peptides processed in these regions.…”
Section: Propertiessupporting
confidence: 90%
“…Stimuli that evoked robust CPE and SgIII release in neurons barely provoked a response in astrocytes. In good agreement with a seminal work analyzing secreted CPE enzymatic activity from Fricker’s lab (Vilijn et al, 1989), we observed no response of released CPE and SgIII to elevated [KCl] o from astrocytes. In addition, increasing [Ca 2+ ] i by ionophores caused variable and weak release responses in glial cells.…”
Section: Discussionsupporting
confidence: 93%
“…A similar activity can also be assumed for Drosophila NEP4 as its potential to degrade neuropeptides (Fig.6), together with a highly specific expression in glia cells (Fig.5N,O) strongly indicate such a physiological relevance. This hypothesis is further corroborated by the general functions of the glia cell subtypes NEP4 is expressed in: while cell body associated glia are structurally similar to mammalian astrocytes (Freeman and Doherty, 2006), lateral glia cells are similar to oligodendrocytes (Stork et al, 2008), with both mammalian cell types reported to be responsible for ion and neurotransmitter homeostasis (Mentlein and Dahms, 1994;Vilijn et al, 1989;Stacey et al, 2007). As no system responsible for the reuptake of neuropeptides at the nerve terminal is known in Drosophila, the biological activity of these transmitters is presumably controlled by extracellular degradation.…”
Section: Isoform Specific Solubility Is Quite Unusual Among Neprilysinsmentioning
confidence: 48%